ANALISIS BIAYA OPERASIONAL KENDARAAN, WILLINGNESS TO PAY DAN ABILITY TO PAY PADA LAYANAN BUS AKAP JURUSAN PALANGKA RAYA - BANJARMASIN - Indrawan, Muhammad Yoggie; Robby, Robby; Supiyan, Supiyan (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
Transportation is one of the essential means of human needs. In this modern era and with the increasing population density in urban areas, transportation is highly necessary to meet an individual's needs in carrying out activities or moving from one place to another, whether it be short distances or long distances. Transportation is the lifeline of national development in facilitating the flow of people, goods, and information as a support for the optimal allocation of economic resources. Therefore, transportation services must be adequately available, evenly distributed, and affordable to the purchasing power of the society. Data on the components of vehicle operational costs were obtained through an interview with the manager of PO. Logos buses, and then the data were analyzed using the Pacific Consultants International (PCI) method, and the amount of vehicle operating costs incurred by PO. Logos. To determine the Ability To Pay (ATP) and Willingness To Pay (WTP) values, the required data is obtained through the distribution of a questionnaire via Google Form, which is filled out by passengers of the PO. Logos bus company. The data analysis results indicate that the operational cost of the vehicle is 15,065.6753/km and the fare based on the Cost of Service (COS) is Rp. 106,811.133, based on the Ability To Pay (ATP) is Rp. 145,054.33, and the Willingness To Pay (WTP) value is Rp. 101,903.00. A primary survey needs to be conducted to obtain the existing load factor value for tariff calculations.